Functional Rehabilitation and Quality of Life After Fibula Free Flap Reconstruction in Mandibular Defects - Fiedler, Mathias; Brunnhuber, Christoph; Eichberger, Jonas; Gottsauner, Maximilian; Schuderer, Johannes G.; Maurer, Michael; Taxis, Jürgen; Meier, Johannes K.; Gerken, Michael; Reichert, Torsten E.; Ettl, Tobias (Journal of Reconstructive Microsurgery, 2025)
Patients undergoing mandibular reconstruction often experience long-term functional and aesthetic challenges, impacting their quality of life (QOL). The objective of this study was to identify factors that most powerfully impact the long-term QOL and functional outcome of patients following mandibular reconstruction with free fibula flaps. This investigation was undertaken to enhance the treatment of this patient population.QOL was assessed between March 2022 and May 2023 in 47 consecutive patients undergoing mandibular reconstruction with fibula free flaps (FFFs) using the University of Washington QOL Questionnaire. Evaluation of functional outcome was based on mouth opening, jaw deviation, tissue atrophy, tongue mobility, lip competence, and speech intelligibility.The study found that loss of chewing was the strongest impairment of QOL (score: 63.83). The most important negative predictors for QOL were female gender (p = 0.047), radiotherapy (QOL subcategory p-values: p = 0.007 to p = 0.034), anterior segment resection (QOL subcategory p-values: p = 0.038 to p = 0.045), advanced defect size (QOL subcategory p-values: p = 0.008 to p = 0.035), and free-hand fibula reconstruction (QOL subcategory p-values: p = 0.003 to p = 0.041). Long-term outcomes revealed that reduced tissue atrophy (QOL subcategory p-values: p < 0.001 to p = 0.025) and preserved tongue mobility (QOL subcategory p-values: p = 0.002 to p = 0.043) were associated with better QOL scores. Functional limitations such as reduced mouth opening (QOL subcategory p-values: p = 0.008 to p = 0.049) and impaired speech intelligibility (QOL subcategory p-values: p < 0.001 to p = 0.015) were significantly correlated with lower QOL in several domains.Mandibular reconstruction with FFFs provides a favorable long-term QOL and functional outcomes, though certain clinical factors, including radiotherapy, anterior segment resection, and defect size, significantly reduce patient-reported QOL.
Keywords: quality of life; fibula free flap; functional outcome